2009
DOI: 10.1002/esp.1913
|View full text |Cite
|
Sign up to set email alerts
|

How do bedform patterns arise? New views on the role of bedform interactions within a set of boundary conditions

Abstract: One explanation for bedform patterns is self-organization in which the pattern emerges because of interactions among the bedforms themselves. Models, remote images, fi eld studies and lab experiments have identifi ed bedform interactions that involve whole bedforms, only bedform defects, or that are remote interactions between bedforms. It is proposed that bedform interactions form a spectrum from constructive to regenerative in pattern development. Constructive interactions, including merging, lateral linking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
181
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(189 citation statements)
references
References 90 publications
(119 reference statements)
7
181
0
1
Order By: Relevance
“…Bedform interactions occur as bedforms or their crestal terminations (defects) approach each other or actually collide. Dune and other bedform interactions have been documented in a range of settings (see review in Kocurek et al [2010]), and pattern emergence and evolution as a function of bedform interactions have been explored in models (e.g., Forrest andHaff 1992, Landry andWerner 1994) and with natural bedforms (e.g., Hersen and Douady 2005, Elbelrhiti et al 2008, Ewing and Kocurek 2010a.…”
Section: Earthmentioning
confidence: 99%
“…Bedform interactions occur as bedforms or their crestal terminations (defects) approach each other or actually collide. Dune and other bedform interactions have been documented in a range of settings (see review in Kocurek et al [2010]), and pattern emergence and evolution as a function of bedform interactions have been explored in models (e.g., Forrest andHaff 1992, Landry andWerner 1994) and with natural bedforms (e.g., Hersen and Douady 2005, Elbelrhiti et al 2008, Ewing and Kocurek 2010a.…”
Section: Earthmentioning
confidence: 99%
“…Beginning with images from the early 1970s, remote sensing (RS) has revealed a rich diversity of dune field patterns on Earth, Mars, Venus, and Titan. The synoptic perspective provided by remote sensing imagery has, however, only recently stimulated a shift away from the singledune studies popularized in the 1980s and 1990s (Livingstone et al, 2007) towards dune field-scale studies that incorporate spatial analysis (SA) of boundary conditions, dune activity, dune patterns and hierarchies, and dune-dune relations (e.g., Tsoar and Blumberg, 2002;Hugenholtz and Wolfe, 2005a;Kocurek and Ewing, 2005;Mitasova et al, 2005;Ewing et al, 2006;Bishop, 2007;Wilkins and Ford, 2007;Ewing and Kocurek, 2010a,b;Hugenholtz and Barchyn, 2010;Kocurek et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in computer hardware and software throughout the 1990s facilitated a shift in study to the reflectance characteristics of dune surfaces (Paisley et al, 1991;Lancaster et al, 1992;Tsoar and Karnieli, 1996;Walden and White, 1997;White et al, 1997;Blumberg, 1998;Pease et al, 1999) and innovative approaches for quantifying historical changes in dune activity (Anthonsen et al, 1996;Brown and Arbogast, 1999). In the last decade, additional progress has been made in the quantitative analysis of dune morphodynamics Vermeesch and Drake, 2008;Bourke et al, 2009;Necsoiu et al, 2009) and dune field pattern analysis (Kocurek and Ewing, 2005;Ewing et al, 2006;Bishop, 2007;Wilkins and Ford, 2007;Mason et al, 2008;Bishop, 2010;Ewing and Kocurek, 2010a,b;Hugenholtz and Barchyn, 2010;Kocurek et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Car transportation rates correspond to sand flux for sediment beds, which is a quantifiable factor. In geomorphology and sedimentology, while interconnectional properties among different levels of interaction (for example, grain−fluid, bedform−fluid, and bedform−bedform) have been identified (e.g., Kocurek et al 2010), differences in the grain-flow phase have not been clearly identified.…”
Section: Comparison With Traffic Flow and Implicationsmentioning
confidence: 99%